EFEK DESTRUCTIVE FISHING OLEH NELAYAN DI KELURAHAN KODINGARENG KECAMATAN SANGKARRANG KOTA MAKASSAR - Suyitno, Iman; Agus, Andi Aco; May Sarah, Huria (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2024)
This research aims to determine, (1) the form of fishing activities categorized as destructive fishing by fishermen in Kodingareng village, (2) to determine the effects caused by destructive fishing by fishermen in Kodingareng village, (3) to find out about prevention and handling efforts related to government agencies’ response to destructive fishing by fishermen in Kodingareng village. This research is a qualitative research and the type of reaserch descriptive . The typesa and sources of data used in this study are primary data sources and secondary data sources. Data collection techniques through interviews and documentation. Data obtained interviews with 6 fishermen, 1 subdistrict secretary and 1 head of the resource supervision and control section marine and fisheries from the Mamminasata Maritime Service Branch. The research used was an interview guide, camera, recording equipment and documentation form. The analysis used is in the form of data collection and reduction data. Presenting data and drawing conckusions.The research results show that (1) the form of fishing activities which is categorized as destructive fishing in Kodingareng village are fishing activities using baraccung (fish bomb explosives), anesthesia and Ghost Fishing. (2) the effects resulting from destructive fishing in Kodingareng village, namely: declain in fish population, (b) destroying reefs coral, (c) decline in the community’s economy, (d) treatens life safety of fishermen. (3) prevention efforts, handling, and institution management government regarding destructive fishing, namely: (a) conducting outreach, (b) patrol integrated, (c) collaboration with Pokmaswas, (d) presents fish houses. Besides there also factors that become obtacles in the government’s efforts tackling destructive fishing activities: destructive fishing raw materials that are sold freely, (b) lack of awarnes of fishermencarriying out destructive fishing